Integrating Augmented Reality into Blended Learning for Improved Magnetism Conceptual Understanding - Asyhari, Ardian; Dian Yusandika, Ajo; Sharov, Sergii (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2024)
In pursuing innovative educational strategies, this study investigates the integration of Augmented Reality (AR) with blended learning to enhance students' conceptual understanding of magnetism. Utilizing AR as a significant educational tool provides an immersive experience that aids in comprehending complex concepts. At the same time, blended learning combines traditional classroom methods with online resources for a more effective approach. This research employs an experimental design with a pretest-posttest control group involving 60 students from the Islamic University of Raden Intan Lampung enrolled in a physics course on magnetism. The experimental group experienced AR-enhanced blended learning, while the control group received traditional blended learning without AR. Quantitative data analysis included descriptive statistics and the N-Gain test to measure the intervention's effectiveness, with ANOVA used to examine differences in conceptual understanding between the groups. Qualitative data was gathered through semi-structured interviews and analyzed thematically to identify common themes and patterns. The results indicate a significant improvement in the experimental group's understanding of magnetism compared to the control group, highlighting AR's effectiveness in enhancing interactivity and engagement, facilitating the visualization of abstract concepts, and reinforcing the linkage between theory and practical application. These findings offer educators and curriculum developers valuable insights, laying a foundation for future interdisciplinary educational research.